First expirience of adalimumab administration in Russia: preliminary results of an open 24 week study - E L Luchichina (Научно-практическая ревматология, 2008)
Introduction. Adalimumab (Humira) is a monoclonal anti-TNFa antibody fully identical to human antibodies, a member of group of TNFa blockers which are now the main biological drugs for the treatment of rheumatoid arthritis (RA). Till recently adalimumab was little known in Russia. Material and methods. 24 pts (2 male and 22 female) were included in an open 24-week clinical study of adalimumab in active RA. Mean duration of the disease was 6,4 years. 5 pts had early RA. In all pts DAS28 was higher than 5,1. All pts earlier received main traditional DMARDs (methotrexate, leflunomide, sulfasalazine) and steroids without significant improvement. All pts were treated on an outpatient basis. Adalimumab 40 mg was injected subcutaneously with 2 weeks intervals during 24 weeks. Results. 22 from 24 pts (91,7%) completed full course of treatment with adalimumab. All outcome measures (pt self assessment on VAS, DAS28,HAQ, CRP) showed fast and sustained improvement. Good effect according to EULAR criteria was achieved in 8 (33,4%), moderate — in 14 (58,3%) pts and 2 pts (8,3%) did not respond to the treatment. Effect did not depend on age, previous treatment, comorbid diseases and disease duration. During follow up period serious adverse events and tuberculosis did not appear in this group of pts. Conclusion. Adalimumab is a highly effective biological drug from the group of TNFa blockers which is particularly useful for the treatment of RA resistant to conventional therapy on an outpatient basis.